(untitled) (Journal of the College of Basic Education, 2023)
In order to reach a specific description of enquiry teaching, we reviewed a group of educational literature related to the subject, and we found a discrepancy in the visions of educators in this regard, and this discrepancy could be due to one or more of the following reasons:(1) The difference of viewpoints among thinkers in the field of teaching about the extent of similarity or congruence between teaching by inquiry and other types of teaching closely related to it, such as teaching by discovery teaching and teaching by problem solving.(2) Variation in the concept of inquiry, despite the fact that the word or term leads to a specific action in the direction of this type of teaching.(3) Many educators tend to use discovery and investigation as synonyms, but it is believed that there are differences between them.The research aims to introduce the concept of inquiry as a teaching method that focuses on the role of the learner more than on the role of the teacher in teaching mathematics, and to compare this concept with the concepts of other teaching methods such as discovery and problem solving.The research sheds light on the importance of investigative thinking as an organized mental process through which the self-activity of the learner can be achieved in educational situations, generating new information, linking and classifying ideas, forming and examining hypotheses, and developing his reflective thinking, in addition to the possibility of investigative thinking in reorganizing ideas into new models that are more solid than the previous ones. at the learner.The research also dealt with types of survey, such as free and directed, and a presentation of the stages or steps of the survey process, with exposure to the most prominent characteristics of the survey, its advantages and shortcomings, and a discussion of the entrances and methods of investigative learning.The research also included a presentation of models of lessons in mathematics in which methods of discovery, investigation and problem-solving were used.